Legal Protection for Buyers of Land Plots in Sidoarjo: Perlindungan Hukum Bagi Pembeli Tanah Kavling Di Sidoarjo - Condro, Rudy; Multazam, M. Tanzil (International Journal of Politic, Public Policy and Environmental Issues, 2023)
This research aims to find out the legal protection for buyers of land plots located in Sidoarjo in the Regulation of the Sidoarjo regent number 59 of 2018 concerning Layout and site plane. The research method used is normative by using a deductive approach, namely the proof of the truth of a statement by proving that a statement is certain to be true. Protection of the sale and purchase of land plots if in a sale and purchase bond can be canceled if the sale and purchase is not in accordance with the Sidoarjo regent Regulation number 59 of 2018 then this can be prosecuted through legal channels under Law number 11 of 2011 article 151 with a criminal sanction of a fine of five billion rupiah and may be subject to additional sanctions to rebuild the site plane in accordance with the criteria, then the purchaser of the land plot can apply for the protection of the buyer of the land plot based on these rules, this research can be concluded that if there is a problem when buying and selling land plots that are not in accordance with the Sidoarjo regulation then Claims and protection rights for land plot buyers can be filed based on the Regent's Regulation